2017
DOI: 10.1177/2309499016684743
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic considerations in scoliosis patient with dopa-responsive dystonia or Segawa’s syndrome

Abstract: Segawa's syndrome or dopa-responsive dystonia is a rare hereditary disorder characterized by progressive dystonia of childhood onset, diurnal fluctuation of symptoms and complete or near complete alleviation of symptoms with administration of low-dose oral levodopa. From our literature search in PubMed, we found only three related publications: two on anesthesia for cesarean section and one on anesthesia for electroconvulsive therapy. We report our experience in providing anesthesia for corrective scoliosis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The safe use of propofol for intravenous general anesthesia has been reported in non-obstetric patients. [10,11] In a cases series of 12 patients with DRD, the author suggested that both succinylcholine and non-depolarizing muscle relaxants were to be tolerated in these patients. [12] Neostigmine and atropine have been reported to counter atracurium muscle relaxant residue in patients with DRD without significant adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The safe use of propofol for intravenous general anesthesia has been reported in non-obstetric patients. [10,11] In a cases series of 12 patients with DRD, the author suggested that both succinylcholine and non-depolarizing muscle relaxants were to be tolerated in these patients. [12] Neostigmine and atropine have been reported to counter atracurium muscle relaxant residue in patients with DRD without significant adverse effects.…”
Section: Discussionmentioning
confidence: 99%